Themes and readability of integrated reports of banks from a circular economy perspective - Keskin, Halit; Esen, Emel (EMERALD GROUP PUBLISHING LTD, 2025)
PurposeThis study examines the themes present in circular economy disclosures that are published in the integrated reports of banks and analyzes their readability scores.Design/methodology/approachFrom 2016 to 2022, a comparative analysis of the integrated reports from six publicly listed Turkish banks that are significant global players was conducted. A total of 21 reports were analyzed, for readability scores and their environmental disclosures from a circular economy perspective were calculated using textual and sentiment analysis techniques.FindingsThe findings of this study underscore the significant involvement of banks in key areas of the circular economy, such as waste management, renewable energy, emission reduction and sustainable financing. Moreover, the study also reveals that the readability of environmental disclosures in the analyzed integrated reports was generally low, suggesting that the information presented may challenge stakeholders and decision-makers and prevent full comprehension, thereby potentially impeding the most effective engagement by stakeholders with circular economy initiatives.Originality/valueThis study introduces a new approach to circular economy reporting by exploring the application of data analytics models when assessing readability within environmental disclosures. It specifically focuses on the context of integrated reporting within the banking sector, an area that has not yet been extensively explored. The study further underscores the importance of clear and concise communication when engaging stakeholders in circular economy efforts. The implications of this research for the banking and environmental sectors thus make this study a valuable addition to the existing literature.
Keywords: Circular economy; Readability; Data analytics; Integrated reporting; Banking sector; CORPORATE SOCIAL-RESPONSIBILITY; BIG DATA; CSR; SUSTAINABILITY; INSIGHTS; IMPACT; Business & Economics